Reforming long-term care in Europe - Costa-i-Font, Joan.; Wiley InterScience (Online service) (Hoboken, NJ : Wiley-Blackwell, 2011)
"Reforming Long-term Care in Europe offers the most up-to-date analysis of the features and developments of long-term care in Europe. Each chapter focuses on a key question in the policy debate in each country and offers a description and analysis of each system. Offers the very latest analysis of long-term care reform agendas in Europe. Compares countries comparatively less studied with the experiences of reform in Germany, the UK, Netherlands and Sweden. Each chapter focuses on a key question in the policy debate in each country and portrays a description and analysis of each system. Contributions from a wide range of European scholars for an exceptionally broad perspective."--
"The assistance given to older people to help with the essential activities of their daily lives is one of the key policy responsibilities undergoing an expansion of public converge. Given the extended life-spans of populations across Europe, this pertinent issue is now increasingly in the loop of political reform in all countries, including the UK, Spain, Germany and Sweden. This book offers the most up-to-date analysis of the features and developments of long-term care in Europe. It focuses on countries that have been comparatively less studied, for example, Eastern Europe, Italy, France and Spain, and makes comparisons with reform practices in Germany, the UK, Netherlands and Sweden. Each chapter focuses on a key question in the policy debate in each country and offers a description and analysis of each system"--
Includes bibliographical references and index.
Print version record.
Keywords: Older people -- Long-term care -- Government policy -- Europe; Older people -- Europe -- Social conditions; Older people -- Government policy -- Europe; SOCIAL SCIENCE -- Sociology -- General; Electronic books